STUDIES ON IN VITRO EVALUATION OF ANTIBACTERIAL ACTIVITIES OF EUCALYPTUS GLOBULUS LABILL LEAF - KHATOON, AKHTARI; ARZOO, ATIA; MOHAPATRA, ASHIRBAD; SATAPATHY, KUNJA BIHARI (International Journal of Current Pharmaceutical Research, 2017)
Objective: The objective of the present investigation was to evaluate the antibacterial potential of n-hexane and methanolic leaf extracts of Eucalyptus globulus Labill. Methods: The antibacterial potential of the leaf extracts were tested against some human pathogenic bacteria causing several diseases such as Staphylococcus aureus, Vibrio cholerae, Pseudomonas aeruginosa, Shigella flexneri, Salmonella typhi, Klebsiella pneumoniae, Salmonella paratyphi, Bacillus subtilis, Micrococcus luteus, Salmonella typhimurium, Escherichia coli, Bacillus circulans, Streptococcus mitis, Enterococcus faecalis by using agar well diffusion method. The concentration of test plant extracts was 20 mg/ml. The inhibitory activity of the leaf extracts was compared with streptomycin as reference antibiotic (RA). The concentration of (RA) was 0.5 mg/ml. Results: The result of the study revealed that n-hexane extract of Eucalyptus globulus Labill. Leaf was highly effective against Micrococcus luteus (19.66±0.94 mm) and least effective against Shigella flexneri (12.33±2.05 mm) whereas the methanolic extract had high inhibition effect against Vibrio cholerae (17.66±1.24 mm) and least against Pseudomonas aeruginosa (10 mm). The zone of inhibition of reference antibiotics ranged between 28.33±0.94 mm (Streptococcus mitis) to 21.66±3.09 mm (Escherichia coli). Conclusion: The leaf extract of E. globulus may be useful as an alternative antimicrobial agent in natural medicine for the treatment of numerous infectious diseases.